Super deformability and Young's modulus of GaAs nanowires. - Wang, Y; Wang, L; Joyce, H; Gao, Q; Liao, X; Mai, Y; Tan, H; Zou, J; Ringer, S; Gao, H; Jagadish, C (2011)
A significant size effect on the mechanical properties of GaAs nanowires (NWs) is reported. A remarkable elastic strain of ≈11% for NWs with diameters of 50-150 nm and obvious plastic deformation in NWs with diameters ≤25 nm are revealed. The Youngs modulus of the NWs can be more than double that of bulk GaAs. Copyright © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.